KONSEP PEMBINAAN ANAK DALAM SURAT LUQMAN MENURUT AL-RAZI PADA TAFSIR MAFÂTÎH AL-GHAIB - Derysmono Derysmono (UIN Mataram, 2021)
The conclusion of this paper is that the development of children in Surat Luqman according to ar-Râzî in the interpretation of Mafâtîh al-Ghaib, includes guidance in: the values ??of faith, understanding religious teachings in a ritual and substantial manner, being devoted to parents, democratic attitudes, consistency and patience in amar ma'ruf nahi munkar, avoiding intellectual, moderate, and communicative arrogance. The concept of fostering religious values ??in a ritual-substantial manner and fostering Muslim character is integrated in an applicative and continuous manner. This paper also reveals that the coaching process starts with the parents, because coaching children requires a successful coach. Luqman is also symbolized by part of the parents, as insân kâmil because of the wisdom,